2019
DOI: 10.1002/slct.201900707
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Palladacycles Containing a Pyrene Chromophor; Synthesis, Biological and Computational Studies of the Interaction with DNA and BSA

Abstract: One of the most active areas within the field of bioorganometallic chemistry, complexes of N-heterocyclic carbenes (NHCs), have recently gained interest. Herein, we report two luminescent palladium N-heterocyclic carbene complexes; namely [Pd {(C,N)-C 6 H 4 CH 2 NH(CH 2 CH 3 )}(1)] (2) and [Pd{(C,N)-C 6 H 4 CH 2 NH 2 }(1)] (3) (1 = 1-methyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-2,3-dihydroimidazol-2-ylidene) which were synthesized from the reaction of luminescent imidazolium salt (1(H)Br) and binuclear Palladacycles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Ltd. 1- N -methyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 1 ) was prepared as reported. 44 [1- N -isopropyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 2 ), 1- N -allyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 3 ) and 1- N -isopropyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium hexafluorophosphate ( 4 ) were newly synthesized by modified procedures. Thin-layer chromatography (TLC) was performed on Merck 1.05554 aluminum sheets precoated with silica gel 60 F254, and the spots were visualized with UV light at 254 nm or under iodine.…”
Section: Methodsmentioning
confidence: 99%
“…Ltd. 1- N -methyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 1 ) was prepared as reported. 44 [1- N -isopropyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 2 ), 1- N -allyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium bromide ( 3 ) and 1- N -isopropyl-3-(2-oxo-2-(pyren-1-yl)ethyl)-imidazolium hexafluorophosphate ( 4 ) were newly synthesized by modified procedures. Thin-layer chromatography (TLC) was performed on Merck 1.05554 aluminum sheets precoated with silica gel 60 F254, and the spots were visualized with UV light at 254 nm or under iodine.…”
Section: Methodsmentioning
confidence: 99%
“…The delicate structural adjustment of IMs toxicity to obtain anticancer activities has led to numerous recent developments, including the conception of N‐ heterocyclic carbenes (NHC), [53–55] whose σ‐donor character highly stabilizes them when complexing transition metals, with no risk of degradation in physiological media. The inclusion of polyaromatic ligands in complexes to obtain biological properties only led to a few studies, [56,57] and the use of these compounds fluorescence to study their interaction with DNA has barely been reported [58,59] …”
Section: Theranosticsmentioning
confidence: 99%
“…Kazeminasab et al [59] . recently produced a rather complete study about a new luminescent NHC ligand ( 4 ) bearing a pyrene fragment, and two complexes ( 5 ) and ( 6 ) based on palladium, binding 4 (Figure 11).…”
Section: Theranosticsmentioning
confidence: 99%
See 2 more Smart Citations